Transitioning from video-assisted to robotic-assisted anatomical pulmonary resection: outcomes from 340 cases in an Australian centre - Shell, Daniel; Firdaus, Mohd; Bunwatcharaphan, Natcha; Gordon, Jacob; Chengalath, Manoras; Yap, Cheng-Hon (Frontiers in Oncology, 2025)
BackgroundRobotic-assisted thoracoscopic surgery (RATS) is emerging as a technically advanced alternative to video-assisted thoracoscopic surgery (VATS) for anatomical pulmonary resection. While its potential benefits include enhanced visualisation and precision, real-world outcome data remain limited—particularly within the Australian healthcare setting. This study evaluates short-term clinical and oncologic outcomes during the transition from VATS to RATS in a single-centre thoracic surgery practice.MethodsWe conducted a retrospective cohort study of 340 consecutive thoracoscopic anatomical lung resections (segmentectomy, lobectomy, or pneumonectomy) performed by a single surgeon between July 2012 and February 2025 in Geelong, Australia. Short-term outcomes from the first 170 patients treated with RATS during the surgeon’s initial robotic experience were compared with those of a historical cohort of 170 VATS patients.ResultsBaseline demographics were similar, although the RATS group included a higher proportion of obese patients and segmentectomies. Both groups demonstrated low complication and mortality rates. RATS was associated with significantly higher lymph node yield (mean 11 vs 8 nodes, p<0.001) and shorter postoperative pleural drainage duration (2.2 vs 3.8 days, p<0.001). Hospital length of stay was reduced by more than two days in the RATS group (4.4 vs 6.4 days, p<0.001). Operative time and rates of conversion, upstaging, and readmission were comparable between groups.ConclusionRATS was safely introduced without increased operative time or complication rates and was associated with improved lymphadenectomy and enhanced postoperative recovery. As the largest Australian comparison of RATS and VATS to date, these findings support the integration of robotic pulmonary resection into standard thoracic surgical practice.